Democratic changes through Dominant Parties: the cases of Federal India, Malaysia, and Mexico - Helder Ferreira do Vale (Revista Debates, 2013)
This article analyzes the dynamics of democratization in India, Malaysia and Mexico. Over thepast decade, these countries, which have been governed by dominant parties, adopted orreinvigorated democratic practices. Unlike the predictions that postulated that democratizationoften occurs in a context of party competition, the article discusses existing mechanisms indominant party systems that force the ruling party to encourage political transformations as asurvival strategy. These three cases reveal that the growing political opposition at the local levelwas a determining factor behind the adoption of democratizing measures by dominant parties.Therefore, the article builds on the relationship between democratization and local opposition indominant party systems.